(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The relevance of the research topic is determined by the visible growing influence of Islamist radicalism in the modern world, which is reflected in activation of the associated socio-political organizations, increasing their outreach capabilities. Today this trend is one of the most complex and intractable problems relating to the Muslim East, where the researchers note the fragility of Eastern-style democracy and strengthening the Islamists position in the government structures. Key words: Islamist movements, sunna, shia, wahhabism, alawites.